(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aimed to identify the relationship between cognitive distortions and pain levels among women with breast cancer. It detects the prevalence of cognitive distortions and its relationship with pain levels according to radiotherapy or chemotherapy applied. (Yurica, 2002) and (NPS) Scales were used, targeting 72 patients in Al-Biruni Hospital-Damascus, with descriptive analytical approach. Results are: The most prevalent distortions were emotional reasoning, perfectionism, emotional reasoning and decision making. (48.57%) of patients treated with radiology felt moderate pain, while (43.24%) of those applying chemotherapy felt low pain. There is a relationship between cognitive distortions and pain levels on the dimensions of exclusion of positive aspects of personality, amplification, marginal thinking, comparison with others. There are differences on the dimensions of perfectionism, emotional reasoning and decision-making due to the educational level and age variables in favor of over fifty years old. There are differences in emotional reasoning and decision-making dimensions in favor of patients applying chemotherapy.